Investigating the Relationship Between Fin and Blue Whale Locations, Zooplankton Concentrations and Hydrothermal Venting on the Juan de Fuca Ridge - Wilcock, William S; Thomson, Richard E (2009)
We are investigating the potential correlation between whale tracks, enhanced zooplankton concentrations and hydrothermal vents above the Juan de Fuca Ridge. Our goal is to understand the influences of globally distributed hydrothermal plumes on the trophic ecology of the deep ocean. Prepared in cooperation with Institute of Ocean SciencesO, Sidney, British Columbia. Code 1 only. The original document contains color images.